The use of blended strategies and speaking skills in students of 1st year BGU at U.E. La Salle, school year 2020 – 2021 - Chuiza Caiza, Stiven Rene (2021)
Communication is a process in which verbalized messages are transmitted using linguistic signs; that is, graphemes and phonemes that involve the use of the word, this is a process between two people in which ideas are exchanged in the form of sounds. In the teaching of the English language, the learner finds it very difficult to verbalize ideas in this language, due to the presence of non-existent phonemes in the Spanish language or due to the lack of agreement between what is written and the way it is pronounced. This research work seeks to determine the incidence of teaching-learning strategies based on blended techniques in the acquisition of speaking skills in first year BGU students of the U.E. “La Salle” During School Year 2020-2021. The importance of any discipline is not measured by the curriculum or the time load, but by adapting the knowledge it offers in due time and the exact proportion (Díaz Bordenave, 1982). Due to this, mixed teaching-learning strategies can be organized to reach the student at the right time for the student and in the amount that suits her learning style and pace. This research work aims to identify the different strategies offered by ICTs, the impact that their use has as part of mixed teachinglearning strategies, and to what extent they can be considered as an effective tool in the improvement of communicative situations in the English language classes. It presents an innovative proposal with activities mediated through tics that involve the development of orality in the English language with a collaborative approach in which everyone participates, communicates, and gets excited while learning orality in the logical context that is required to learn any language, ie vocabulary, and grammar. The project is structured in four chapters........